Synchronous Triple Cancers of the Pancreas, Stomach, and Cecum Treated with S-1 Followed by Pancrelipase Treatment of Pancreatic Exocrine Insufficiency - Ohtsubo, Koushiro; Ishikawa, Daisuke; Nanjo, Shigeki; Takeuchi, Shinji; Yamada, Tadaaki; Mouri, Hisatsugu; Yamashita, Kaname; Yasumoto, Kazuo; Gabata, Toshifumi; Matsui, Osamu; et al. (JOP. Journal of the Pancreas, 2013)
Context Pancreatic cancer is frequently complicated by malignancies in other organs. However, synchronous triple cancers including pancreatic cancer have been seldom reported in the English language literature. Case report We describe the rare case of a 77-year-old man with triple cancers of the pancreas, stomach, and cecum. Biopsies revealed that all three tumors were adenocarcinomas. The pancreatic and gastric tumors were positive for cytokeratin 7 and negative for cytokeratin 20, whereas the cecal tumor was negative for cytokeratin 7 and positive for cytokeratin 20. K-ras mutations were present at codon 12 in the pancreatic tumor and at codon 13 in the cecal tumor, but were absent from the gastric tumor. Since the three tumors had different characteristics, the patient was diagnosed with synchronous triple cancers. Because invasive surgery was required to remove all three tumors and the patient had risk factors for surgery, we elected to treat him with chemotherapy. All three cancers were markedly reduced in size by treatment with cycles of 100 mg/day S-1 for 2 weeks, followed by a 1-week rest. The patient later developed hypoproteinemia and anasarca, which was diagnosed as pancreatic exocrine insufficiency due to pancreatic head cancer. Treatment with pancrelipase resulted in dramatic improvements in hypoproteinemia and anasarca. Conclusions This is the first case report in which S-1 was effective in triple cancers of the pancreas, stomach, and cecum. Patients with pancreatic head cancer should be monitored for pancreatic exocrine insufficiency. Image: Gastric tumor in the middle part of the stomach.